2013
DOI: 10.1080/03630242.2013.782940
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of Physical Activity on Inflammatory Biomarkers in Women With or Without Metabolic Disorders: A Systematic Review

Abstract: Overwhelming data support the relationship between physical inactivity and inflammatory processes underlying metabolic disorders. The aim of this review was to assess critically the body of evidence for the relationships between exercise protocols and levels of inflammatory biomarkers in women. Systematic literature searches using PubMed Medline, Cochrane Central Register of Controlled Trials, Web of Science, LILACS, and SciELO of publications from 1993 to January 2012 were conducted using the following keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Thus, the effects of regular physical activity on basal levels of inflammatory markers have been used to recommend exercise as an anti-inflammatory therapy. According to Soares and de Souza [14] integrative interventions, including diet, moderate aerobic exercise (60% to 80% of HRmax or 50% to 60% of VO 2max⁡ ) and circuit resistance training (8 to 10 exercises, 8 to 12 repetitions), health education, and counseling, used together, appeared to be effective strategies to improve inflammatory biomarkers in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the effects of regular physical activity on basal levels of inflammatory markers have been used to recommend exercise as an anti-inflammatory therapy. According to Soares and de Souza [14] integrative interventions, including diet, moderate aerobic exercise (60% to 80% of HRmax or 50% to 60% of VO 2max⁡ ) and circuit resistance training (8 to 10 exercises, 8 to 12 repetitions), health education, and counseling, used together, appeared to be effective strategies to improve inflammatory biomarkers in women.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that regular physical activity induces multiple adaptations within skeletal muscles and the cardiorespiratory system, providing positive outcomes for the prevention and treatment of chronic diseases [7, 8]. Some studies have indicated that regular physical activity has anti-inflammatory effects and is associated with improvement in inflammatory biomarkers such as a reduction in levels of the proinflammatory cytokines [914]. According to Pedersen [8], the anti-inflammatory processes provided by physical exercise play important roles in the protection against diseases associated with low-grade inflammation such as cardiovascular diseases and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…It was stated by Krintus et al [41] that the complex multifactorial cause of CHD goes beyond inflammatory risk factors to include factors such as electrocardiogram results, lipid profile, renal function, and imaging and clinical parameters. Favourable modification of inflammatory risk factors is of major interest, and Soares and de Sousa [42] reviewed 15 selected articles with women as the protagonists and found that 12 of 15 articles showed decreased inflammatory biomarkers in association with exercise. Inflammatory risk status was the major factor in the Justification for the Use of statins in Primary prevention: an Intervention Trial Evaluating Rosuvastatin (JUPITER) trial.…”
Section: Inflammationmentioning
confidence: 99%
“…A systemic review investigating the efficacy of different types of exercise interventions on inflammatory biomarkers in females with metabolic disorders showed that aerobic training and integrated therapeutic lifestyle management – which encompasses both regimented exercise routines and alterations to negative lifestyle practices, such as smoking and poor diet – provided the greatest positive gains compared with resistance training or acute aerobic exercise, which possessed minimal efficacy or were deleterious, respectively . Furthermore, they reported that the maximal benefit was achieved when participants engaged in moderate intensity (60–80% of maximal heart rate) and moderate duration exercise (45–80 min, two or three times weekly).…”
Section: Exercise As a Therapy For Cns Disorders: Lessons From Systemmentioning
confidence: 99%